Analisis Manajemen Risiko pada Bank Syariah: Implementasi dan Tantangan Risiko Syariah - Oktaviani, Yeyen; Huda, Nurul (UNIVERSITAS SERAMBI MEKKAH, 2025)
Risk management is a set of comprehensive policies and procedures owned by an organization to manage, monitor, and control its exposure to risks. Risk is defined as the uncertainty arising from changes. The methodology used in this research is library research, with a descriptive qualitative approach. Additionally, the data source for this research is secondary data, which consists of previous relevant scholarly works, including books and other academic writings from various perspectives. In its implementation, risk management in Islamic banking includes risk identification, risk measurement, monitoring, and controlling risks. In this context, various forms of risk must be faced, including credit risk, market risk, liquidity risk, as well as compliance and operational risks. The application of risk management at all levels, whether on a small or large scale, is crucial as it can reduce the likelihood of risks and errors in the long term.